2022
DOI: 10.3390/cancers14030839
|View full text |Cite
|
Sign up to set email alerts
|

Role of CBL Mutations in Cancer and Non-Malignant Phenotype

Abstract: CBL plays a key role in different cell pathways, mainly related to cancer onset and progression, hematopoietic development and T cell receptor regulation. Somatic CBL mutations have been reported in a variety of malignancies, ranging from acute myeloid leukemia to lung cancer. Growing evidence have defined the clinical spectrum of germline CBL mutations configuring the so-called CBL syndrome; a cancer-predisposing condition that also includes multisystemic involvement characterized by variable phenotypic expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…We found that subject III.3 experienced an episode of pericarditis, occurred about 20 years after transplantation. The attribution of this pericarditis to CBL syndrome is controversial, since this clinical manifestation has not previously been reported in the disorder [ 23 ]. Moreover, subject III.3 received HSCT from the sister carrying wild-type CBL gene and a healthy immune system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that subject III.3 experienced an episode of pericarditis, occurred about 20 years after transplantation. The attribution of this pericarditis to CBL syndrome is controversial, since this clinical manifestation has not previously been reported in the disorder [ 23 ]. Moreover, subject III.3 received HSCT from the sister carrying wild-type CBL gene and a healthy immune system.…”
Section: Resultsmentioning
confidence: 99%
“…Variants in SH2B3 were also described in autoimmune diseases, particularly autoimmune type 1 diabetes [ 22 ]. CBL and SH2B3 are functionally related, contributing to the modulation of signal strength promoted by JAK proteins [ 23 ]. We herein report a family segregating pathogenic variants in CBL and SH2B3 presenting novel clinical features, particularly related to immune dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…The c-cbl proto-oncogene was identified as the cellular homolog of the murine retroviral oncogene v-cbl. [22] Its gene product, Cbl, is a 906-amino acid protein that contains two distinct regions, Cbl-N and Cbl-C. [23] Composed of amino acids 1-357, Cbl-N is evolutionarily conserved and has been shown to bind many autophosphorylated tyrosine kinases in a phosphotyrosine-dependent manner. [24] Cbl-C includes evolutionarily conserved regions and a non-conserved proline-rich region capable of interacting with the Src homology 3 (SH3) domain of Src family kinases, Grb2, and Nck adaptor proteins.…”
Section: Discussionmentioning
confidence: 99%
“…CBL variants were of particular interest, as they were not previously reported in pediatric cancer genomics, but have been established in a variant-associated tumor predisposition syndrome (Fig. 5e) 39 . In addition, other genetic variants frequently found in cancer were identi ed including MYC or MYCN mutations (one ampli cation each, 5%) and disease speci c gene fusions including PAX3-FOXO1 in alveolar rhabdomyosarcoma (two of two patients, 100%) and EWSR-FLI1 fusions in Ewing's sarcoma (two of four patients, 50%) (Fig.…”
Section: Genomic Tumor Pro Ling Actionability and Ex Vivo Correlationmentioning
confidence: 98%